2014
DOI: 10.3109/0142159x.2014.889814
|View full text |Cite
|
Sign up to set email alerts
|

Developing questionnaires for educational research: AMEE Guide No. 87

Abstract: In this AMEE Guide, we consider the design and development of self-administered surveys, commonly called questionnaires. Questionnaires are widely employed in medical education research. Unfortunately, the processes used to develop such questionnaires vary in quality and lack consistent, rigorous standards. Consequently, the quality of the questionnaires used in medical education research is highly variable. To address this problem, this AMEE Guide presents a systematic, seven-step process for designing high-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
790
0
25

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 942 publications
(819 citation statements)
references
References 29 publications
4
790
0
25
Order By: Relevance
“…One of the steps in curriculum development involves establishing content validity of content [23–25]. This step determines whether the content measures the construct (i.e., core SHE knowledge) for the intended population (i.e., learners in the medical education continuum).…”
Section: Methodsmentioning
confidence: 99%
“…One of the steps in curriculum development involves establishing content validity of content [23–25]. This step determines whether the content measures the construct (i.e., core SHE knowledge) for the intended population (i.e., learners in the medical education continuum).…”
Section: Methodsmentioning
confidence: 99%
“…Von Reisswitz et al In this study, the content validity of the Turkish version of the instrument was established with the evidence obtained from expert opinions. This stage involved collecting data from content experts to establish that the individual survey items were relevant to the construct being measured and that key items or indicators had not been omitted (9). Content validity ratios based on the experts' opinion indicated that all the items in the instrument were in compliance with the measurement purpose.…”
Section: Discussionmentioning
confidence: 99%
“…When an instrument is developed or adapted to a different language, its validity and reliability should be established because specific studies may require a comprehensive linguistic translation process, but this still does not ensure construct validity and reliability (8,9). If an instrument developed in one culture is to be used in another culture correctly, establishment of its validity and reliability in the new culture is a prerequisite.…”
Section: Introductionmentioning
confidence: 99%
“…This descriptive, cross-sectional study was conducted at Mysore Medical College & Research Institute, Mysore using a predesigned questionnaire which was duly modified to suit the local situation and keeping the Medical Council of India vision 2015 document in mind [6][7][8][9][10]. First part (Question No.1-12) of the questionnaire related to importance of basic science subjects, time duration, vastness, clinical applicability, recall aspects, which were to be answered on a 5 point Likert scale (strongly disagree, disagree, neutral, agree, strongly agree).…”
Section: Methodsmentioning
confidence: 99%